2017
DOI: 10.15637/jlecon.216
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Attitudes of Tax Amnesty Non-Beneficiaries and Tax Amnesty Beneficiaries: Evidence From Turkey

Abstract: Tax amnesties are applied by many countries on different grounds throughout the world. Governments want to realize social, political, economic, etc. purposes through tax amnesties. It is important that some matters should be clarified within the scope of being realized of these purposes. One of these matters is related to attitudes of tax amnesty non-beneficiaries and tax amnesty beneficiaries. Within this framework, this research aims to reveal attitudinal tendencies of tax amnesty non-beneficiaries and tax a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The result of this research showed that the tax amnesty in Indonesia was successful and had a significantly impact on the country's economy. The alternative study done by Gergerlioğlu (2017, p. 46) [7] shows that both the beneficiaries of tax amnesty and the non-beneficiaries of tax amnesty gives similar opinion regarding statements about tax amnesties. Based on the results of this research, the majority of beneficiaries of tax amnesty and non-beneficiaries argue that revenues from tax amnesties contribute significantly to state treasury.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result of this research showed that the tax amnesty in Indonesia was successful and had a significantly impact on the country's economy. The alternative study done by Gergerlioğlu (2017, p. 46) [7] shows that both the beneficiaries of tax amnesty and the non-beneficiaries of tax amnesty gives similar opinion regarding statements about tax amnesties. Based on the results of this research, the majority of beneficiaries of tax amnesty and non-beneficiaries argue that revenues from tax amnesties contribute significantly to state treasury.…”
Section: Literature Reviewmentioning
confidence: 99%